(untitled) (New York, 2002)
The book is holden the most comprehensive and effective guide available for the CompTIA Network+ exam. A crack team of networking experts delivers incisive, crystal-clear explanations of every Network+ topic, highlighting exam-critical concepts and offering hands-on tips that can help the real-world networking career. Throughout, they provide pre-tests, exam-style assessment questions, scenario problems, and labs - everything you need to master the material and pass the exam. Inside, you'll find complete coverage of Network+ exam objectives.
Keywords: Electronic data processing personnel,Computer networks,Mạng lưới máy tính,Xử lý dữ liệu điện tử nhân sự; Certification,Examinations,Sách hướng dẫn,Giấy chứng nhận